Negotiating cultural and legal demands in child protection cases: Experiences and lessons from Ghanaian social workers - John Boulard Forkuor; Alice Konadu-Yiadom; Eric Agyemang; Charles Selorm Deku; Douglas Attoh Odongo (Cogent Social Sciences, 2024)
Within the context of globalization, social workers need to ensure that international-level professional knowledge and practice do not lead to the oppression of the local people that the profession seeks to serve. One of the challenges for social workers is how to negotiate the sometimes-competing definitions and demands of local and cultural norms versus global and international laws. In this study, we used qualitative methods to explore those instances that bring to the fore the contentions between cultural and legal rights in child welfare cases in Ghana. Evidence from the study revealed that these social workers were faced with three main instances where conflict usually arose when navigating between the law and the culture of the people: (a) child custody disputes, (b) child paternity tests, and (c) child marriage. One of the key findings is that social workers adopt a benefit-emphasis approach to sensitise families and communities about the benefits of the legal requirements that guide and protect children. In doing so, they try to avoid any form of condemnation or attack on the norms and values of the people. The importance of this approach lies in its tact to de-emphasize the need to label right or wrong and emphasize the benefits of, for instance, educating the girl child for the family. We argue that using the benefit-emphasis approach is a key strategy for negotiating cultural and legal demands in child protection cases in Ghana.